Ghetto cowboy - Neri, Greg (Candlewick Press, 2013)
Twelve-year-old Cole's behavior causes his mother to drive him from Detroit to Philadelphia to live with a father he has never known, but who soon has Cole involved with a group of African-American "cowboys" who rescue horses and use them to steer youths away from drugs and gangs.